2014
DOI: 10.1155/2014/748549
|View full text |Cite
|
Sign up to set email alerts
|

Abrus precatoriusLeaves: Antioxidant Activity in Food and Biological Systems, pH, and Temperature Stability

Abstract: Natural antioxidants present in foods and other biological materials have attracted considerable interest because of their presumed safety and potential nutritional and therapeutic effects. Antioxidant constituents of plant materials act as radical scavengers and convert the radicals to less reactive species. Abrus precatorius (AP) was analyzed for its proximate and phytochemical composition. The leaves were extracted with methanol (ME) and analyzed for antioxidant activity by radical scavenging method, reduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…Studies also report that they exhibit good antioxidant activity in vitro [13, 31] Table 1 depicts the phytochemical composition of the samples, where it was observed that CS and AnP were good sources of polyphenols, glutathione, β -carotene, total saponins, and steroidal saponins, whereas AP and CP were found to be good sources of flavonoids, alkaloids, α -tocopherol, vitamin C, and tannins.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies also report that they exhibit good antioxidant activity in vitro [13, 31] Table 1 depicts the phytochemical composition of the samples, where it was observed that CS and AnP were good sources of polyphenols, glutathione, β -carotene, total saponins, and steroidal saponins, whereas AP and CP were found to be good sources of flavonoids, alkaloids, α -tocopherol, vitamin C, and tannins.…”
Section: Resultsmentioning
confidence: 99%
“…Other medicinal plants, namely, Morus indica [9], Moringa oleifera , Aegle marmelos [10], Raphanus sativus , olive leaves [11], pomegranate peel [11], Costus speciosus [12], Canthium parviflorum [12], and Abrus precatorius [13] leaf extracts, have effectively inhibited the rate of oxidation in the edible oil emulsions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Society has shown increasing interest in natural antioxidants, since these may be safer than the synthetic ones (Reddy Palvai et al ., ). Antioxidants can be intended to many applications in the food industry, among them it could be mentioned the lipid oxidation prevention and browning prevention, as functional ingredients, and antimicrobials (Ayala‐Zavala et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…The whole plant has been used as a folk medicine for controlling fevers, removing toxicity, preventing jaundice as well as treating infectious hepatitis [ 1 ]. Previous studies have also demonstrated the potential biological activities of this plant, including antioxidant [ 2 ], anti-tumor [ 3 ], antimicrobial [ 4 ], hepatoprotective [ 5 ], and immunomodulatory activities [ 6 ].…”
Section: Introductionmentioning
confidence: 99%